Introduction to modern cryptography - Katz, Jonathan, 1974-; Lindell, Yehuda (Chapman & Hall/CRC cryptography and network security, 2008)
"Cryptography plays a key role in ensuring the privacy and integrity of data and the security of computer networks. Introduction to Modern Cryptography provides a rigorous yet accessible treatment of modern cryptography, with a focus on formal definitions, precise assumptions, and rigorous proofs."--